2020
DOI: 10.1177/2045894019897513
|View full text |Cite
|
Sign up to set email alerts
|

Understanding longitudinal biventricular structural and functional changes in a pulmonary hypertension Sugen–hypoxia rat model by cardiac magnetic resonance imaging

Abstract: Cardiac magnetic resonance-derived ventricular variables are predictive of mortality in pulmonary arterial hypertension. Rodent models which emphasize ventricular function, allowing serial monitoring, are needed to identify pathophysiological features and novel therapies for pulmonary arterial hypertension. We investigated longitudinal changes in the Sugen–hypoxia model during disease progression. Sprague Dawley rats ( n = 32) were divided into two groups. (1) Sugen–hypoxia: a dose of subcutaneous Sugen-5416 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Our Su/Hx rat model replicated the lower RVEF observed in a modified Su/Hx mouse protocol carried 22 as well as within clinic in PAH patients. 26 Previously, our group had undertaken CMRs in Su/Hx rats, 13 which found no changes in RVEF. Possible reasons for this difference are the previous study had a shorter 2-week hypoxic phase and it is previously been published that increasing the duration of hypoxia significantly modifies PH indices in Su/Hx rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our Su/Hx rat model replicated the lower RVEF observed in a modified Su/Hx mouse protocol carried 22 as well as within clinic in PAH patients. 26 Previously, our group had undertaken CMRs in Su/Hx rats, 13 which found no changes in RVEF. Possible reasons for this difference are the previous study had a shorter 2-week hypoxic phase and it is previously been published that increasing the duration of hypoxia significantly modifies PH indices in Su/Hx rats.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CMR in animal models could provide more accurate measurements of ventricular volumes and function 12 . This has been demonstrated recently by our own group in the Su/Hx rat model 13 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Proteomics analysis revealed that a significant downregulation of adenylate kinase 1 (ADK1), which translates into inefficient cardiac energetics, might be the molecular substrate for the premature deterioration of RV function in Fisher rats [ 86 ]. In Sprague Dawley rats, RV hypertrophy and increased filling pressures are present after 5 weeks, with a subsequent RV enlargement by 8 weeks, but still preserved RV stroke volume and ejection fraction [ 85 ]. Rodent hypoxia-based pulmonary hypertension models have been exhaustively addressed by several reviews [ 79 , 84 , 138 ].…”
Section: Pressure Overload Modelsmentioning
confidence: 99%
“…Cardiac function was measured in rats anesthetized with isoflurane, briefly, the catheter was inserted into the jugular vein, and guided into the right ventricle, then hemodynamic data were measured, include RVSP (Right Ventricular Systolic Pressure), max dp/dt and min dp/dt [11,12], heart rate (HR), right ventricular end-diastolic pressure (RVEDP), pulmonary artery systolic pressure, mean pulmonary artery pressure. The right ventricle and the left ventricle plus interventricular septum were separated and weighed respectively to calculate RV/(LV+S) as right ventricular hypertrophy index.…”
Section: Measurement Of Cardiac Functionmentioning
confidence: 99%